Teaching cultural geography in the elementary school a case study - Peradilla, Angelina B. (2006)
Heograpiya, Kasaysayan at Sibika (HKS) 4 curriculum is centered on the geographic component but the competencies concerning the physical and cultural aspects are not equally emphasized. The objectives of this research include the content analysis of the HKS 4 Learning Competencies and the development of instructional materials that utilize local resources and different teaching strategies in teaching selected lessons in cultural geography. Fifteen HKS teachers of grade four from Batangas City evaluated the materials, and was tried out to one section of grade four pupils in Kumintang Elementary School. The 15 teachers evaluated the 8 teaching exemplars as very good enrichment materials.